C♯ .Net Web developer's guide (Syngress Media, 2002)
Microsoft's C# ("C sharp") is a modern, object-oriented programming language built from the ground up to exploit the power of XML-based Web services on Microsoft's new .NET platform. With its Visual C++ development system heritage, C# will enable millions of C and C++ developers to use existing skills to rapidly build sophisticated XML-based .NET applications. C#.net Web Developer's Guide will enhance developer productivity and help them eliminate programming errors that can lead to increased development costs. This book teaches Web developers to quickly and easily build solutions for the Microsoft .NET platform. Web developers will learn to use C# components to build Web services and applications that are available across the Internet, from any application running on any platform.